2017
DOI: 10.1177/0963689717731574
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Assessment of Animal-free Collagenase AF-1 for Human Islet Isolation

Abstract: Animal-free (AF) SERVA Collagenase AF-1 and Neutral Protease (NP) AF GMP Grade have recently become available for human islet isolation. This report describes the initial experiences of 3 different islet transplant centers. Thirty-four human pancreases were digested using 1 vial of the 6 different lots of Collagenase AF-1 (2,000–2,583 PZ-U/vial) supplemented with 4 different lots of NP AF in a range of 50 to 160 DMC-U per pancreas. Isolation, culture, and quality assessment were performed using standard techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…We detected a significant increase in isolation success over the last years when comparing with the period between 2008 and 2013. This result is in accordance with a recent report of the Collaborative Islet and Transplantation Registry, 5 and is probably explained by improvements in the commercially available collagenase blends 16,23 . IGL‐1 has become the most commonly used preservation solution in recent years.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We detected a significant increase in isolation success over the last years when comparing with the period between 2008 and 2013. This result is in accordance with a recent report of the Collaborative Islet and Transplantation Registry, 5 and is probably explained by improvements in the commercially available collagenase blends 16,23 . IGL‐1 has become the most commonly used preservation solution in recent years.…”
Section: Discussionsupporting
confidence: 90%
“…Toso et al reported that CIT >8 hours and ORT (secondary warm ischemia time) >30 minutes was associated with a reduced islet yield 10 . These two studies were published over 15 years ago, and significant advances in the development of novel enzyme blends may have contributed to mitigate the impact of parameters previously shown as deleterious 16,23 . In a more recent study, Berkova et al reported among other variables that a CIT >8 hours had significant adverse effects on isolation success 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite a higher yield, the collagenase-based MSC isolation technique from bone marrow biopsy specimens will not immediately replace the manufacturing of therapeutic MSC batches starting from bone marrow aspirates because most collagenase preperations are still poorly standardized [37] and bear the risk of transmiting infectious diseases [38].…”
Section: Discussionmentioning
confidence: 99%
“…Many consider the preparation required for cellular transplantation as a significant disadvantage, and the numerous steps of islet isolation are illustrative (Table 3). 10 Similarly, as described below, other cellular transplants will need continued basic and clinical research to achieve reproducible preparation for broad application 11,12 …”
Section: Advantages and Disadvantages Of Cellular Versus Solid Organ Transplantationmentioning
confidence: 99%